Czy jest homoseksualizm w tym tekście? Na tropach nieheteronormatywnej tożsamości bohaterów "Kamieni na szaniec" Aleksandra Kamińskiego = - Rawski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Interpretation of the relationship Tadeusz Zawadzki ?Zośka? and Jan Bytnar ?Rudy? ? heroes Stones for the rampart by Alexander Kaminski made by Elizabeth Janicka, according to which the two men combined homoerotic love, caused the Polish literary environment and media controversy. On the one hand, there are calls for ?tarnish the national holiness?, on the other hand, other environmental endorsed a model of reading the text.
Keywords: Kamiński, Aleksander (1903-1978); homoseksualizm; "Kamienie na szaniec"